Human improvement and criminal liability: new challenges in treating guilt and dangerous - Gómez Lanz, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The purpose of this analysis is to examine —naturally, in an introductory way— what the impact of eventual advances may be on transhumanist objectives in the field of criminal responsibility. In my opinion, the analysis of the possible consequences of transhumanism in the domain of criminal law affects two different spheres: (i) first, it can affect the factors that, nowadays, underlie the imputation of criminal responsibility; (ii) on the other hand, it is necessary to address the repercussion that transhumanism could have no longer in the trial for the imputation of criminal responsibility, but in the determination of the consequences assigned to those criminally responsible and in their execution process. As will be seen later, this reflection today raises more questions than answers.
Keywords: Transhumanism; Criminal responsibility; Criminal responsibility system; Capacity and responsibility; Legal improvement